2023
DOI: 10.7759/cureus.35686
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Immunohistochemistry Expression of E-cadherin, Beta-Catenin, and CD44 in Colorectal Adenocarcinoma

Abstract: Background Colorectal cancer is a leading cause of cancer-related deaths worldwide, and epithelial-mesenchymal transition (EMT) plays an important role in cancer metastasis. In EMT, there is downregulation of E-cadherin, an intracellular adhesion molecule, as well as mutations in beta-catenin genes. On immunohistochemistry (IHC), the expression of CD44 portrays stem cell differentiation, which, in turn, is strongly associated with EMT. Thus, newer targeted therapies can be advised based on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Increased expression of β-catenin showed a strong association with increasing grading and staging of the tumor with lymph node metastases, which was also seen in the studies by Choi et al 21 and Tunuguntla et al 25 and decreased expression in adenomas. However, no such association was found in other studies by Gomaa et al 23 Our result showed the gradual intracellular translocation of β-catenin from a membranous to a nuclear expression in a stepwise manner, following the polyp-adenoma-carcinoma sequence, which is in concordance with the findings of Wong et al 28 In this study a statistically significant changes in the subcellular localization and increase in β-catenin expression was noted between benign and malignant neoplasms, with the subsequent presence of a higher nuclear β-catenin score in the malignant neoplasms.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Increased expression of β-catenin showed a strong association with increasing grading and staging of the tumor with lymph node metastases, which was also seen in the studies by Choi et al 21 and Tunuguntla et al 25 and decreased expression in adenomas. However, no such association was found in other studies by Gomaa et al 23 Our result showed the gradual intracellular translocation of β-catenin from a membranous to a nuclear expression in a stepwise manner, following the polyp-adenoma-carcinoma sequence, which is in concordance with the findings of Wong et al 28 In this study a statistically significant changes in the subcellular localization and increase in β-catenin expression was noted between benign and malignant neoplasms, with the subsequent presence of a higher nuclear β-catenin score in the malignant neoplasms.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with the studies by Iseki et al 22 , Gomaa et al 23 , and Melincovici et al 24 had a male predominance. Conversely, the studies by Choi et al 21 and Tunuguntla et al 25 show female preponderance. In the present study, 52.9% of malignant cases were considered T3 stage, and similar findings were observed by Gomaa et al 23 , Melincovici et al 24 and Tunuguntla et al 25 , whereas the T4 stage was the major type in the study by Iseki et al 22 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Conventional prognostic parameters for CRC include tumor staging and grading, metastases, and, additionally, lymphatic, perineural, and venous invasion. However, one study also assessed E-cadherin expression depending on these markers, and it turned out that most CRC patients had tumors with low (60%) E-cadherin expression, which was significantly associated with a higher T stage, the presence of lymph node metastasis, and TNM staging [ 4 ]. In another recent study, the immunohistochemical staining, protein expression, and mRNA level of E-cadherin were lower in tumors than in normal tissues, and the expression levels of E-cadherin were significantly associated with the pathological classification, lymph node, distal metastasis, and TNM stage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%